Desafios na medição da tensão limite de escoamento de óleos parafínicos - Tarcha, Bruno Amaral (2014)
Non-Newtonian fluids formed by dispersion, as emulsions, solutions and gels, can manifestviscoelastic, plastic and thixotropic characteristics. When the waxy crude oil is subjected tolow temperatures, its paraffin particles precipitate, creating a resistant structure. Understandingtheir behavior in this critical condition is essential to analyze the production restart of wells andpipelines, which are of high economic interests. The design of pumps and compressores usedin these systems depend on a rheological property called yield stress. The complexity of thebehavior and dependence on the history of shear and temperature, make the evaluations com-plex, inaccurate and of low repeatability. The present work was developed through experimentson a commercial stress control rheometer, using a cone-plate geometry. The selected fluid wasa waxy crude oil produced in the brazilian coast, exposed in laboratory to thermal conditionsrepresentative of events experienced by the industry. In an attempt to develop a suitable proce-dure for measuring the breakdown stress of the gelled structure, tests with impose stresses andshear rates were performed, when three typical stresses were identified: elastic, static and dyna-mic. The one related to the rupture of the material, an event of interest in the industry, is calledthe static yield stress, whose measurements showed good agreement between different typesof tests. The results also showed particular behaviors of the material at different deformationconditions, such as viscoelasticity at low rates and purely viscous effects at high rates. Varioustypes of experiments, preceded by thermal treatment and shear were developed over time, butstill there is not a definitive procedure available for these materials. This work presents theadvantages of the imposition of stress in relation to shear rate, mainly due to the use of a stresscontrol rheometer. It is also shown the importance of considering the time dependent nature of xistructured materials, as the high influence of this variable was seen on the results. The mate-rial reversibility is tested by specific procedures and the structure rebuild was not relevant onthe experiments duration. The consistency of results was evaluated previously, when a lack ofsignificant slipping effects was observed, as the absence of evaporation or aging of the sampleduring the tests and also the actual equipment capability of controlling and measuring.